Shared decision making for psychiatric medication management: beyond the micro‐social. (10th August 2015) - Morant, Nicola; Kaminskiy, Emma; Ramon, Shulamit
Abstract: Background: Mental health care has lagged behind other health‐care domains in developing and applying shared decision making (SDM) for treatment decisions. This is despite compatibilities with ideals of modern mental health care such as self‐management and recovery‐oriented practice, and growing policy‐level interest. Psychiatric medication is a mainstay of mental health treatment, but there are known problems with prescribing practices, and service users report feeling uninvolved in medication decisions and concerned about adverse effects. SDM has potential to produce better tailoring of psychiatric medication to individuals' needs. Objectives: This conceptual review argues that several aspects of mental health care that differ from other health‐care contexts (e.g. forms of coercion, questions about service users' insight and disempowerment) may impact on processes and possibilities for SDM. It is therefore problematic to uncritically import models of SDM developed in other health‐care contexts. We argue that decision making for psychiatric medication is better understood in a broader way that moves beyond the micro‐social focus of a medical consultation. Contextualizing specific medication‐related consultations within longer term relationships, and broader service systems enables recognition of the multiple processes, actors and agendas that shape how psychiatric medication is prescribed, managed and used, and which may facilitate or impede SDM. Conclusion: A broad conceptualization of decision making for psychiatric medication that moves beyond the micro‐social can account for why SDM in this domain remains a rarity. It has both conceptual and practical utility for evaluating research evidence, identifying future research priorities and highlighting fruitful ways of developing and implementing SDM in mental health care.